2015
DOI: 10.2217/pgs.15.126
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Pain-Related Single Nucleotide Polymorphisms in Patients of African Origin with Sickle Cell Disease

Abstract: Background Prospective pain genetics research is hindered by a lack of data on the prevalence of polymorphisms in pain-relevant genes for patients with sickle cell disease (SCD). For African–Americans in general, limited information is available in public databases. Methods We prioritized and examined the genotype and allele frequencies of 115 SNPs from 49 candidate pain genes in 199 adult African–Americans and pediatric patients of African origin with SCD. Analyses were performed and compared with available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Co-inheritance of α-thalassaemia has been inconsistently associated to variable levels of VOC (Platt et al , 1991; Darbari et al , 2012; Tarer et al , 2006). In addition, a few observational studies have explored the associations of VOC with targeted variants in genes coding for enzymes that metabolize analgesics or inflammation-related proteins, with encouraging results (Hu et al , 2016; Jhun et al , 2015; Mendonça et al , 2010; Belfer et al , 2014; Galarneau et al , 2013). Specifically, one study identified and prioritised a total of 115 single nucleotide polymorphisms (SNPs) in 49 candidate genes that modified pain among African-American SCD patients (Jhun et al , 2015); but this has not been followed by genotype to phenotype investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Co-inheritance of α-thalassaemia has been inconsistently associated to variable levels of VOC (Platt et al , 1991; Darbari et al , 2012; Tarer et al , 2006). In addition, a few observational studies have explored the associations of VOC with targeted variants in genes coding for enzymes that metabolize analgesics or inflammation-related proteins, with encouraging results (Hu et al , 2016; Jhun et al , 2015; Mendonça et al , 2010; Belfer et al , 2014; Galarneau et al , 2013). Specifically, one study identified and prioritised a total of 115 single nucleotide polymorphisms (SNPs) in 49 candidate genes that modified pain among African-American SCD patients (Jhun et al , 2015); but this has not been followed by genotype to phenotype investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published, (Jhun et al, 2015) reported on patients with SCD from two institutions who participated in a pain study exploring pain phenotypes. The population consisted of African American adults and pediatrics patients of African origin.…”
Section: Resultsmentioning
confidence: 99%
“…Arginine vasopressin is a 7-transmembrane domain G-protein polypeptide that has been identified as being involved in many neurological functions, including aggression, bonding, sex behavior, autism, and schizophrenia (Kreek, Zhou, & Levran, 2011). The single nucleotide polymorphism (SNP) of the arginine vasopressin receptor 1A (AVPR1A) gene (rs10877969), is one of 115 polymorphisms of 49 genes that were previously identified as a candidate pain SNP (Jhun et al, 2015). A SNP is a common type of base pair substitution, which may cause changes in protein expression that lead to differences in response to drugs, appearances, and response to environment.…”
mentioning
confidence: 99%
“…However, known polymorphisms in the COMT , OPRM1 , and ABCB1 genes can lead to an altered perception of pain and/or a change in response to opioids. 17 , 18 Additionally, the pharmacokinetics of opioids can be altered by genetically mediated variability in the activity of CYP enzymes and by organ dysfunction of SCD. This combination of factors results in a complicated clinical presentation.…”
Section: Opioidsmentioning
confidence: 99%